DETERMINANTS OF FOOD SECURITY AMONG INDONESIAN FARMING HOUSEHOLDS - Septiani, Yustirania; Iskandar, Deden Dinar (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
The Global Food Security Index (GFSI) shows an increase in Indonesia's food security from 2021 to 2022. However, this increase does not yet indicate better Indonesian food security because this increase is still lower than the global average and the Asia Pacific average. The food security conditions of farming households could be a solution considering the importance of farming household food security which can deliver an impact in maintaining economic stability and reducing dependence on the market. This research aims to analyze the factors that influence the food security of farming households. The model used is Robust Regression since the Normality and Heteroscedasticity assumptions were failed. Data were taken from IFLS wave 5. Based on the results, it shows that the variables of age, gender, home ownership status, cooking fuels, electricity use and house location influence the food security of farming households. While, the variables of head of household’s education, availability of toilets and water sources have no effect on the food security of farming households